Oncostatin M suppresses IL31RA expression in dorsal root ganglia and interleukin-31-induced itching - Suehiro, Masataka; Numata, Tomofumi; Saito, Ryo; Yanagida, Nozomi; Ishikawa, Chie; Uchida, Kazue; Kawaguchi, Tomoko; Yanase, Yuhki; Ishiuji, Yozo; McGrath, John; Tanaka, Akio (Frontiers in Immunology, 2023)
Background Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by intermittent itchy rash. Type 2 inflammatory cytokines such as interleukin (IL)-4, IL-13, and IL-31 are strongly implicated in AD pathogenesis. Stimulation of IL-31 cognate receptors on C-fiber nerve endings is believed to activate neurons in the dorsal root ganglion (DRG), causing itch. The IL-31 receptor is a heterodimer of OSMRβ and IL31RA subunits, and OSMRβ can also bind oncostatin M (OSM), a pro-inflammatory cytokine released by monocytes/macrophages, dendritic cells, and T lymphocytes. Further, OSM expression is enhanced in the skin lesions of AD and psoriasis vulgaris patients. Objective The current study aimed to examine the contributions of OSM to AD pathogenesis and symptom expression. Methods The expression levels of the OSM gene (OSM) and various cytokine receptor genes were measured in human patient skin samples, isolated human monocytes, mouse skin samples, and mouse DRG by RT-qPCR. Itching responses to various pruritogens were measured in mice by counting scratching episodes. Results We confirmed overexpression of OSM in skin lesions of patients with AD and psoriasis vulgaris. Monocytes isolated from the blood of healthy subjects overexpressed OSM upon stimulation with IL-4 or GM-CSF. Systemic administration of OSM suppressed IL31RA expression in the mouse DRG and IL-31-stimulated scratching behavior. In contrast, systemic administration of OSM increased the expression of IL-4- and IL-13-related receptors in the DRG. Conclusion These results suggest that OSM is an important cytokine in the regulation of skin monocytes, promoting the actions of IL-4 and IL-13 in the DRG and suppressing the action of IL-31. It is speculated that OSM released from monocytes in skin modulates the sensitivity of DRG neurons to type 2 inflammatory cytokines and thereby the severity of AD-associated skin itch.